The influence of delipidation on triglyceride and LIPIN1 of porcine embryos derived from parthenogenetic activation. (29th April 2017) - Zeng, Y; Wang, C; Niu, Y; Chi, D; Xu, M; Si, L; Qu, X; Li, J
Contents: Proteins in the LIPIN family play key roles in lipid synthesis mainly on triacylglycerol (TAG) biosynthesis, and they also act as transcriptional coactivators to regulate the expression of genes involved in lipid metabolism with other nuclear factors. Hence, this study was designed to investigate LIPIN1 in pig oocytes and embryos by the delipidation. After delipidation, the content of lipids (LDs) and TAG in MII oocyte was significantly reduced; however, a similar increasing tendency of TAG was shown during embryos development. Subsequently, the expression of genes related to TAG biosynthesis including GPAT1, AGPAT1, AGPAT2, LIPIN1, DGAT and the nuclear factors interacted with LIPIN1 including PPARα and PPARγ was investigated. It is obvious that DGAT and GPAT1, and LIPIN1 increased significantly after delipidation at 1‐cell and 4‐cell stage, and the expression of PPARα and PPARγ also increased at 4‐cell stage. By immunofluorescence staining and Western blots, LIPIN1 was found to exhibit a dynamic localization pattern and gradually increase with the development of delipated embryo. In the early developmental stages (1‐, 2‐ and 4‐cell stages), it was distributed over the cortical layer. But at the blastocyst stage, a homogeneous distribution of LIPIN1 was observed in cytoplasm. At 2‐cell stage, the expression of PPARα decreased when LIPIN1 was interfered by small interfering RNA, but PPARγ has no significant difference. Therefore, in this study, we find after delipidation, the content of TAG and LIPIN1 will gradually increase during embryo development and nuclear factor PPARα and PPARγ can also be affected by delipidation. The interaction of LIPIN1 and PPARα exists in porcine embryo.